A new perspective of frozen shoulder pathology; the interplay between the brain and the immune system - Navarro-Ledesma, Santiago; Hamed-Hamed, Dina; Pruimboom, Leo (Frontiers in Physiology, 2024)
Frozen shoulder (FS), also known as adhesive capsulitis of the shoulder (FS), is a fibrotic inflammatory process of unknown etiology whose main symptoms are pain, stiffness and the loss of joint mobility. These symptoms may be associated with pathologies such as diabetes, Dupuytren's syndrome and the prevalence of today's sedentary lifestyle. This literature review provides an overview of the epidemiology and pathogenesis of this pathology, as well as the mechanisms of lowgrade chronic inflammation and infection, insulin resistance, and omics-science associated with it. We also propose a new hypothesis related to the possibility that the GABAergic system could play a decisive role in the development of frozen shoulder and that therefore diabetes type 1, endocrinological autoimmune disorders and frozen shoulder are connected by the same pathophysiological mechanisms.If that is true, the combined presence of psycho-emotional stress factors and pathogenic immune challenges could be the main causes of frozen shoulder syndrome. Finally, we propose a series of possible intervention strategies based on a multifactorial etiological and mechanistic concept.Dear Dr. Feilong Wang We are pleased to present the manuscript entitled: Metabolomics in frozen shoulder pathology: A path to be explored. A review of the literature whose main objective is to main objective is to analyze the existing scientific evidence on the epidemiology and pathogenesis of this pathology, as well as on the mechanisms of chronic low-grade inflammation and infection, insulin resistance and metabolomics associated with it. In addition to the investigation of different metabolites characteristic of adhesive shoulder capsulitis that could help to better understand this pathology. We believe that this study is of great interest to the readers of the Journal of Frontiers Physiology. This review also proposes different intervention strategies as part of a multifactorial treatment. This information could be of great importance, since taking into account this proposal, more effective treatment strategies could be established for this patient profile.We thank you for the considerable effort involved in reviewing this manuscript, and we look forward to your response. Yours sincerely,